Letters and papers relating to the publication of the Australian encyclopaedia (1917)
The 2 volume 'Australian Encyclopedia' was edited by Arthur Wilberforce Jose and Herbert James Carter, with the collaboration of T. G. Tucker, and published in 1925-1926. This collection of encyclopedia pre-publication material contains correspondence of Herbert James Carter, Arthur Wilberforce Jose, N. Lockyer, R. J. Tillyard, Sidney H. Ray, T. G. Tucker, Sir Archibald Strong, W. Ramsay Smith, Dr. Griffith Taylor and W. Baldwin Spenser.
Manuscript reference no. : NLA MS 708.
Keywords: Tucker, T. G. -- Correspondence; Jose, Arthur W. -- 1863-1934 -- Correspondence; Carter, Herbert James -- Correspondence; Australian encyclopaedia